Empowering Women of 'Aisyiyah Wonosari in Preventing Microplastics Impacts on Reproductive Health - Rozifa, Annisa' Wigati; Novembriani , Rizqie Putri; Yumni , Fathiya Luthfil (LP2M INSURI Ponorogo, 2025)
Microplastics have emerged as a significant threat to human health, particularly affecting the female reproductive system. This community service program aimed to increase the knowledge of ‘Aisyiyah Members in Wonosari, Bondowoso, about the dangers of microplastics and to encourage the adoption of a healthy and environmentally friendly lifestyle. The program employed a participatory, community-based approach that included socialization, education, and training sessions focusing on reproductive health and household waste management. The team employed interactive methods, including PowerPoint presentations, posters, and guidebooks, to enhance engagement and foster a deeper understanding. They implemented a pre- and post-test design to measure the improvement in knowledge among 51 participants. The results showed an 80% increase in participants' knowledge regarding the dangers of microplastics and their impacts on reproductive health. The establishment of the